Variables with the highest incidence and domestic violence in Peru - Risco Franco, Carlos (2009)
This paper is a descriptive-analytical study using factor analysis and cluster analysis on domestic violence in Peru based on the 2004-2007 DHS of the INEI. The conclusions show that there are different levels of domestic violence, according to groups of departments, and tentative maps of Peru are drawn up showing the variations in emotional, physical and sexual violence affecting 50% of households in the country as a whole.